The Effect of Text Feature Walks Strategy and Reading Interest on High School Students’ Reading Comprehension of Expository Text - Shella Monica; Badeni Badeni; Sayfnil Arsyad; Muhammad Kristiawan; Azizatul Khairi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aim at (1) analyzing the use of text feature walks strategy in improving students’ reading comprehension (2) analyzing the effect of text feature walks strategy on students’ reading interest (3) finding out the effect of text feature walks strategy and reading interest on the students’ reading comprehension achievement. This experimental research uses 2x2 factorial designs which are involved two groups: control and experimental groups. 60 high school students in Lubuklinggau, Indonesia were selected as the participant in this study. The instruments used for collecting the data were reading comprehension test and reading interest questioner. Moreover, the findings show that there were a significant difference that shows positive improvement in reading comprehension achievement between the students who were taught by using text feature walks strategy and those who were not. Then, by comparing the post-test scores, it was recognized that positive effect of the implementation of text feature walks strategy was also shown on the students’ reading interest. In the other hand, based the result of two-way ANOVA analysis it was indicated that there was no significant effect of Text feature walks strategy and reading interest on reading comprehension achievement.